OCCUPATIONAL HAZARD PERCEPTION AND SAFETY PRACTICES AMONG WORKERS OF SMALL-SCALE INDUSTRIES IN KANO, NIGERIA - Lawan UM; Gajida AU; Ibrahim UM; Gora MM (Ntec Specialist, 2016)
Background: Work-related injuries present a major public health problem resulting in serious social and economic consequences that could be prevented by adopting appropriate occupational health and safety measures. Objective: This study assessed occupational hazard perception, safety practices and associated factors among workers of small scale industries in Kano. Method: A descriptive cross-sectional design was used to study 187 randomly selected workers of Small Scale Industries. Data was collected using interviewer administered semi-structured questionnaire and analyzed with IBM SPSS Statistics for Windows, version 22. Results: The mean age of the workers was 24.41 ± 6.20 years with a range of 15 to 52 years. A third of the workers (35.3%) had at least secondary school education and most (88.3%) had worked for 10 years or less. Overall, 95.7% of the workers have good perception about occupational hazards and safety and 92.0% believed that exposure to hazards of work may affect their health. Up to 67.9% of the respondents reported being caught-up in at least one form of occupational accident, most common were dislocation (39.4%) and burns (19.7%). Most of the workers (97.3%) reported that their industries do not have any policy on health and safety and 73.8% had never been trained or advised on safety procedures. Only 49(26.2%) reported having safety measure(s) against specific accidents in their workplaces. Conclusion: Most SSIs in Kano do not have policy on health and safety. Factory inspectors should ensure effective compliance monitoring and enforcement of safety guidelines in these industries